Removal of heavy metal ions from aqueous solutions using natural waste materials - Mohammed Wissam Shukr Khanjar; Ghufran Haider Hassan AbdNoor; zahraa jaleel kharebeat Aboud; Eman Hassan Ashour Suhail; Arwa Hassan Nassar Farhan (Genius Journals, 2024)
Due to the development that has occurred in recent decades in aspects of industry and agricultural techniques, and the increase in population growth, this has led to an increase in various wastes that are discharged into natural systems, especially the water of rivers, seas, and oceans, which in turn affects the lives of animals, plants, and humans alike. In this research, the theory of water pollution with heavy metals was studied, and its sources of contamination of water bodies and their impact on humans, animals, and plants alike were mentioned. The chemical and physical methods used to remove these pollutants (heavy metals) were also discussed. The study showed that physical methods are the best in removing heavy metal ions in terms of their effectiveness, ease of reactivation and reuse. Adsorption processes using plant waste are considered low in cost and pollution and can be easily disposed of.
Keywords: Heavy Metal; Agricultural Techniques; Pollution